Pembangkit Listrik Tenaga Air (PLTA) Portable Berbasis IoT - Iyullela Siregar, Novela Sucira; Khozin, Nur; Sulistyo, Eko; Surojo, Surojo (Jurnal Inovasi Teknologi Terapan, 2023)
Based on the increasing need for electricity for the community, especially in the Bangka Belitung region, which still uses a lot of expensive fossil energy (generators), so it is still a cost constraint for people living in remote areas that have not been electrified. So it is necessary to innovate in making electricity that utilises natural resources (water). However, the problem is that water sources in some places have erratic water discharge. Therefore, in this research it is proposed to make a portable hydropower plant so that it can be moved in a place that has a high water discharge that can monitor the rpm, voltage and current of the generator and battery and is expected to be used as a cheap and environmentally friendly alternative power plant. The methodology in making this hydropower plant uses a 100Watt DC generator with a 12-bladed breadshot turbine type and is controlled using LM393 sensors and INA219 sensors with a monitoring system using the Blynk application by utilising IoT-based technology. The test was conducted by testing the effect of generator rpm speed on generator current and voltage, battery charging and discharging time, and testing the monitoring system using the Blynk application. From the test results, it is obtained that the minimum generator rpm that must be achieved when charging the battery is 425 rpm with the power obtained of 12.19Watt. Charging a 50 Ah capacity battery at the hydropower plant takes 6 hour and 38 minutes with a charging current of 6,7A. While for battery discharge using a 12V 75Watt lamp load takes 7 hours 25 minutes. The generator monitoring system using the Blynk application works well in displaying the same measurement results on the LCD screen with an accuracy value of 100%.